Formal Modulation for Acoustic Performances of a Bridge - Tiazzoldi, Caterina; Tixier, Nicolas (Enquiry The ARCC Journal for Architectural Research, 2008)
In the last fifteen years in architecture the frequent use of design instruments such as algorithms,dynamical relations, parametric systems, mapping, morphogenesis, cellular automata and bifurcationwith broken symmetry shows clearly how contemporary thinking in mathematics andphysical sciences, dealing with complex dynamics, non-linear systems, chaos, emergent properties,resilience, etc., has changed the way we think about design and the life of today's cities.